The Balance and the Mind study: baseline data - van der Wardt, Veronika; Logan, Pip; Booth, Victoria; Hood, Victoria; Masud, Tahir; Harwood, Rowan H. (Elsevier, 2015)
OBJECTIVES: The purpose of the study was to establish falls risk factors for people with mild cognitive impairment and mild dementia. METHODS: Survey of 76 people recruited from Memory Clinics (n=56), Falls Services (n=12), Community Geriatricians (n=4), Cognitive Stimulation Therapy groups (n=2), and a Rehabilitation Unit (n=2). The assessments included falls risk, the Falls Efficacy Scale International (FESi), the Montreal Cognitive Assessment (MoCA) as well as neuropsychological tests. RESULTS: Mean age was 80.9 years (SD 6.5, age range: 67-94 years). The sample included 45% men, 98% had a white ethnic background and 48% lived alone. Mean MoCA score was 20.95 (SD 3.6), and 26 people (34%) had between 1 and 24 falls (mean 3.04; SD 4.65). Regarding any fall participants had in the past, 41% sustained an injury, 36% needed medical attention and 32% had been admitted to hospital as a consequence of a fall. The mean FESi score was 27 (SD 10.6) with 59% scoring >23, which is associated with a high fear of falling. The mean Timed Up and Go score was 16.0 seconds with 44% scoring ≥13.5 seconds, which is associated with high risk of falling. The mean Berg Balance score was 46 with 28% scoring ≤40, which is associated with a 100% chance of future falls. All assessments were acceptable to the particpants. CONCLUSIONS: The proportion of falls and falls risk factors was quite high in this population, which reflects findings from similar studies. Specialized falls prevention intervention should take these factors into account.